(untitled) (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
We study quasi-stationary distributions (q.s.d.) for Markov chains. We review some recent results relating q.s.d. Yaglom limit and limit distributions conditioned to non absorption.